Research on Access Layer Communication Line Design Based on PON Technology - Du, Jun (Journal of Artificial Intelligence and Information, 2025)
Since the network structure becomes more and more perfect, the public has put forward many requirements regarding the communication quality of the access layer. However, if the access layer communication still uses the traditional techniques to design the line, the communication quality cannot be guaranteed to meet the public requirements. Therefore, PON technology should be flexibly integrated into the line design, and the technical advantages should be used to strengthen the communication quality fundamentally. To further analyze the design of access layer communication line based on PON technology, this paper first introduces the basic concepts of PON technology and access layer, then puts forward the key points of design of access layer communication line based on PON technology, and finally points out the specific design method of access layer communication line with a case as the core.